Do Polarization Narratives Apply to Politics on the Periphery? The Case of Atlantic Canada - McLay, Rachel; Ramos, Howard (Frontiers in Sociology, 2021)
Researchers, policymakers, and the public often claim that “extreme” political views have become increasingly commonplace and that polarization on issues of race and immigration has become a central dilemma for contemporary politics. The popular narrative of political polarization captures tensions that many are noticing and experiencing. However, there is also significant confusion around the concept, as well as gaps between popular perceptions and empirical findings on the different forms of polarization and their prevalence across regions. It is unclear to what extent polarization describes a global phenomenon, as its national and subnational manifestations vary considerably, produced from distinct local histories as well as diffuse transnational forces. While the United States is often treated as ground zero for political polarization, nearby Canada does not appear to be experiencing polarization to nearly the same degree. Using data from a 2019 survey on Atlantic Canadians’ political views and perceptions of change, this paper examines whether underlying forms of political polarization are manifesting in the region. We assess whether mass ideological polarization and partisan sorting can be found in Atlantic Canada, looking at socio-cultural and economic dimensions of political values. We also examine perceptions of polarization in the region, using Multiple Correspondence Analysis to observe underlying associations between perceptions, extreme or polarized views, and partisanship. This mapping approach provides insight into latent patterns often missed by more traditional methods.